CONCEPTUAL MODELS DEVELOPMENT FOR ENVIRONMENTAL RISKS ASSESSMENT - Franchuk Grigory М.; Radomska Мargaryta М. (Proceedings of National Aviation University (archive), 2008)
The basics of conceptual models are presented in the article. Practical application of environmental conceptual models to the process of environmental risks assessment process is given. Structural issues of models formation are presented and most common types of conceptual models are analyzed. Recommendations for site-specific models construction are developed for various organizational levels and types of receptors. The scheme for integration of ecological conceptual model with conceptual model for the industrial site is presented and approaches to making them consistent with the conceptual model of human health risks are stated.